El tipo legal del delito de receptación aduanera del art. 300 del COIP vulnera el debido proceso - Lindao Sellán, Andrea Elizabeth (2020)
On February 10, 2014, the Comprehensive Organic Penal Code enters into force and with it the crime of customs reception, criminal conduct contemplated and codified in article 300, and which is part of the crimes against the customs administration, among the elements that characterize this type of conduct is simulation, deception, falsehood, hoarding and concealment of impact and induce errors in the customs administration. For its part, with the entry into force of the Constitution of the Republic in 2008, our legal system became a guarantee system that seeks to protect citizens from violations of their rights fully recognized in the content of the supreme rule, however, Sometimes the regulations in force in our justice system produce a systematic violation of these rights, causing civil society to be in a state of violation by the normative body that makes it up............